Dissociating vestibular and somatosensory contributions to spatial orientation - Alberts, Bart B. G. T.; Selen, Luc P. J.; Bertolini, Giovanni; Straumann, Dominik; Medendorp, W. Pieter; Tarnutzer, Alexander A. (Journal of neurophysiology, 2016)
Inferring object orientation in the surroundings heavily depends on our internal sense of direction of gravity. Previous research showed that this sense is based on the integration of multiple information sources, including visual, vestibular (otolithic), and somatosensory signals. The individual noise characteristics and contributions of these sensors can be studied using spatial orientation tasks, such as the subjective visual vertical (SVV) task. A recent study reported that patients with complete bilateral vestibular loss perform similar as healthy controls on these tasks, from which it was conjectured that the noise levels of both otoliths and body somatosensors are roll-tilt dependent. Here, we tested this hypothesis in 10 healthy human subjects by roll tilting the head relative to the body to dissociate tilt-angle dependencies of otolith and somatosensory noise. Using a psychometric approach, we measured the perceived orientation, and its variability, of a briefly flashed line relative to the gravitational vertical (SVV). Measurements were taken at multiple body-in-space orientations (−90 to 90°, steps of 30°) and head-on-body roll tilts (30° left ear down, aligned, 30° right ear down). Results showed that verticality perception is processed in a head-in-space reference frame, with a systematic SVV error that increased with larger head-in-space orientations. Variability patterns indicated a larger contribution of the otolith organs around upright and a more substantial contribution of the body somatosensors at larger body-in-space roll tilts. Simulations show that these findings are consistent with a statistical model that involves tilt-dependent noise levels of both otolith and somatosensory signals, confirming dynamic shifts in the weights of sensory inputs with tilt angle.